Implementasi Perjanjian Tertulis dalam Kegiatan Sewa Menyewa Lahan Pertanian : Studi Kasus di di Desa Taman, Kecamatan Jrengik, Kabupaten Sampang - Gracia Tribuana Wibowo; Sumriyah Sumriyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The urgency of arranging written contracts in business practice is to ensure that the exchange of interests (rights and obligations) takes place proportionally for the parties, and to provide legal certainty that can guarantee that the parties are not harmed by each other, so that a fair contractual relationship can be established. and mutually beneficial. Not the other way around, harming one of the parties or even ultimately harming the contracting parties. Likewise, with the commercial contracts which are the focus of this research, simply questioning contractual imbalances based on the sound of the contract clauses actually goes against the essence of the contractual relationship built by the parties. In commercial contracts, the aim of the parties is more aimed at building business relationships that are fair and do not harm each other. Rentals of agricultural land involving farmers and also the community who own the land should be contained in a written contract containing clauses that have been agreed upon by the parties to obtain legal certainty. The urgency of arranging written contracts in business practice is to ensure that the exchange of interests (rights and obligations) takes place proportionally for the parties, and to provide legal certainty that can guarantee that the parties are not harmed by each other, so that a fair contractual relationship can be established. and mutually beneficial. Not the other way around, harming one of the parties or even ultimately harming the contracting parties. Likewise, with the commercial contracts which are the focus of this research, simply questioning contractual imbalances based on the sound of the contract clauses actually goes against the essence of the contractual relationship built by the parties. In commercial contracts, the aim of the parties is more aimed at building business relationships that are fair and do not harm each other. Rentals of agricultural land involving farmers and also the community who own the land should be contained in a written contract containing clauses that have been agreed upon by the parties to obtain legal certainty.